2014
DOI: 10.1021/jo500691b
|View full text |Cite
|
Sign up to set email alerts
|

Hypervalent Iodine-Promoted α-Fluorination of Acetophenone Derivatives with a Triethylamine·HF Complex

Abstract: The direct fluorination reaction of acetophenone using iodosylarenes and TEA·5HF was conducted under mild conditions except for use of a HF reagent. The fluorination reaction was applied to acetophenone derivatives, acetonaphthones, benzyl phenyl ketone, propiophenone, butyrophenone, 1-indanone, and phenacyl chloride, giving selectively the corresponding α-fluoroketone derivatives in good yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…Moreover, elegant studies by Hara and co-workers have demonstrated that α-fluoroketones could be prepared by exposing silyl enol ethers to stoichiometric p -ToIIF 2 , in the presence of BF 3 ·OEt 2 and NEt 3 /HF 1:2 [ 38 ]. A report by Kitamura and co-workers in which the direct fluorination of acetophenone derivatives was achieved using iodosylarenes and commercially available NEt 3 /HF 1:5 to generate the ArIF 2 species in situ is also highly pertinent [ 39 40 ] ( Fig. 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, elegant studies by Hara and co-workers have demonstrated that α-fluoroketones could be prepared by exposing silyl enol ethers to stoichiometric p -ToIIF 2 , in the presence of BF 3 ·OEt 2 and NEt 3 /HF 1:2 [ 38 ]. A report by Kitamura and co-workers in which the direct fluorination of acetophenone derivatives was achieved using iodosylarenes and commercially available NEt 3 /HF 1:5 to generate the ArIF 2 species in situ is also highly pertinent [ 39 40 ] ( Fig. 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…Based on the results of the above control experiments as well as the previous reports,, we postulated a plausible mechanistic pathways for this PhIO/Et 3 N ⋅ 3HF‐mediated tandem oxidation reaction, described in Scheme . Initially, the reaction between PhIO and Et 3 N ⋅ 3HF gave PhIF 2 species, which reacts with the enamine substrate 1 to give the α ‐iodo imine B .…”
Section: Methodsmentioning
confidence: 57%
“…[22] First, PhIO is activated by Et 2 O • BF 3 to form an iodine(III) intermediate (50), which reacts with 48 a to give an iodonium intermediate (51), followed by intramolecular nucleophilic attack of the amino group to generate 52. Then, the hypervalent iodine(III) intermediate (52) undergoes reductive elimination to afford a cyclic carbocation intermediate (53). Subsequent combination of 53 with the in situ generated fluoride provides the final product (49 a).…”
Section: Amino- Oxy-or Carbofluorination Of Alkenesmentioning
confidence: 99%
“…Likewise, direct fluorination of acetophenone derivatives, acetonaphthones, benzyl phenyl ketone, propiophenone, butyrophenone, 1‐indanone, and phenacyl chloride ( 145 ) with iodosylarenes and TEA ⋅ 5HF (TEA=Et 3 N) gave selectively the corresponding α‐fluoroketone derivatives ( 146 ) in good yields (Scheme ) . The use of easily available iodosylarenes and a safer TEA ⋅ 5HF complex led to a greener fluorination reaction.…”
Section: Fluorination Mediated By Hypervalent Iodine Reagentsmentioning
confidence: 99%